PET image reconstruction using MRI-based anatomical priors:application to the Siemens 3T MR-BrainPET system - Caldeira, Liliana Lourenço 1984- (2013)
Tese de doutoramento, Engenharia Biomédica e Biofísica, Universidade de Lisboa, Faculdade de Ciências, 2013